RELATIONSHIP BETWEEN KB INJECTION 3 MONTHS WITH SPOTTING EVENTS IN BPM MUJIYEN VILLAGE GABAHAN SUBSCRIBE BANYUDONO REGENCY OF BOYOLALI - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2018)
Background : Injectable contraception in the most popular alternative because it is easy to use and practice. Injectable contraception that most popular is injectable contraception three months that is given in every three months and also consist of progestin hormone without estrogen. KB injection three months has the high level of success, but also it has the effects, one of the effects is the menstrual disorders. Aim of the research : To know about how strong the relationship between the used of KB injection three months and getting of spotting in BPM Mujiyem, Gabahan Village Banyudono, Boyolali. Research Design : This research is survey analytical with cross sectional by quantitative the population in this research was all of the acceptor who used KB in BPM Mujiyem of Gabahan Village, Banyudono, Boyolali it was about 867 acceptor. The sampling technique is using purposive sampling, 90 respondents. Gathering of datas by using opened questionnaire that consist of the used KB Injection three months, age, job, paritas, spotting, and history of spotting. To analyze the data used univariat and bivariat analysis. Result : The result of this research showed that there is relationship between the used of KB Injection Three Months and spotting in 0,019 (p<0,05). The contingency coefficients is 0,019, it means that the relation between the used of KB Injection Three Months and spotting very low. Conclusion : The used of KB injection three month causes the effects in menstrual disorders, it is spotting. The suggestion for the health workers before giving the contraception service they have to give conseling about the contraception that will be used